2017
DOI: 10.1021/acs.joc.7b00438
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of HIV-Maturation Inhibitor BMS-955176 from Betulin by an Enabling Oxidation Strategy

Abstract: A concise and scalable second generation synthesis of HIV maturation inhibitor BMS-955176 is described. The synthesis is framed by an oxidation strategy highlighted by a Cu mediated aerobic oxidation of betulin, a highly selective PIFA mediated dehydrogenation of an oxime, and a subsequent Lossen rearrangement which occurs through a unique reaction mechanism for the installation of the C17 amino functionality. The synthetic route proceeds in 7 steps with 47% overall yield and begins from the abundant and inexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…A concise and scalable synthesis of 64 starting from betulin in seven steps and 47% overall yield has been described. The synthesis is framed by an oxidation strategy highlighted by a CuI‐mediated aerobic oxidation of betulin, a highly selective PIF‐mediated dehydrogenation of an oxime, and a subsequent Lossen rearrangement, which occurs through a unique reaction mechanism for the installation of the C‐17 amino functionality 64 . Compound 64 demonstrated better anti‐HIV potency than BVM with no significant safety issues in its Phase IIa studies.…”
Section: Pentacyclic Triterpenoidmentioning
confidence: 99%
See 1 more Smart Citation
“…A concise and scalable synthesis of 64 starting from betulin in seven steps and 47% overall yield has been described. The synthesis is framed by an oxidation strategy highlighted by a CuI‐mediated aerobic oxidation of betulin, a highly selective PIF‐mediated dehydrogenation of an oxime, and a subsequent Lossen rearrangement, which occurs through a unique reaction mechanism for the installation of the C‐17 amino functionality 64 . Compound 64 demonstrated better anti‐HIV potency than BVM with no significant safety issues in its Phase IIa studies.…”
Section: Pentacyclic Triterpenoidmentioning
confidence: 99%
“…The rational design of substituents linked to the C-3 and C-28 positions of betulinic acid and analogs is critical in attaining new derivatives with improved anti-HIV activity. Although the development of BVMas the first-in-class HIV-1 maturation inhibitor was halted due to the high baseline drug resistance of HIV-1 variants with polymorphism, further studies identified the second-generation maturation BMS-955176(64), which showed significantly improved anti-HIV activity toward BVM-resistant variants. Unfortunately, the development of BMS-955176 was also discontinued by the pharmaceutical company GSK for gastrointestinal intolerance and treatment-emergent drug resistance by patients.…”
mentioning
confidence: 99%
“…A concise and scalable second-generation synthesis of HIV maturation inhibitor 64 (Scheme 9) was published in 2017 [66]. The synthesis was based on an oxidation strategy involving a CuI mediated aerobic oxidation of betulin ( 2 ), a highly selective PIFA mediated dehydrogenation of an oxime, and a subsequent Lossen rearrangement, which occurred through a unique reaction mechanism for the installation of the C17 amino functionality.…”
Section: Derivatives Of Betulinic Acid Their Pharmacological Effementioning
confidence: 99%
“…The synthesis was based on an oxidation strategy involving a CuI mediated aerobic oxidation of betulin ( 2 ), a highly selective PIFA mediated dehydrogenation of an oxime, and a subsequent Lossen rearrangement, which occurred through a unique reaction mechanism for the installation of the C17 amino functionality. The synthetic procedure consisted of seven steps with a 47% overall yield and it begins from the abundant and inexpensive natural product betulin ( 2 ) (Scheme 9) [66]. The target compound 64 became a potent HIV-1 inhibitor in cell culture that exhibited a broad spectrum of antiviral effects that encompass the V370A- and ΔV370-containing polymorphic viruses.…”
Section: Derivatives Of Betulinic Acid Their Pharmacological Effementioning
confidence: 99%
“…Betulinic acid (BA) as shown in Figure 1 and its derivatives, has been known as a potent group to inhibit HIV-protease (Aiken and Chen, 2005). Modification to enhance BA derivatives' protease inhibition were conducted by some previous studies (Kashiwada et al, 1996;Zhao et al, 2012;Ortiz et al, 2017;Huang et al, 2018). The changes of substituent on the C-28 position have been recognized to give different HIVprotease inhibition.…”
Section: Introductionmentioning
confidence: 99%